Collisions: Negotiating tensions in a shared marketplace. Issue 2 (12th December 2018) - Pryor, Susie; Adkins, Natalie Ross
Abstract : Nonprofit organizations (NPOs) operate within marketing systems comprising broader networks of individuals, groups, and/or entities linked through shared participation in economic exchanges. These systems include diverse constituents with varied goals and orientations. Inherently, tensions arise as NPOs, for‐profit firms, and other social actors pursue differing agendas, often competing for finite resources. In this paper, we report the results of an ethnographic study, which examines one community's efforts to alleviate these tensions as they occur in a downtown business district. The area is noted for its economic vitality and diversity, but struggles to accommodate the needs of the homeless population and the social service agencies who maintain a presence there. Relationships between multiple constituencies erode as the business community seeks to displace both the social service agencies and the individuals they serve. The community in this study moved through thematic stages of problem solving associated with contentious social issues. They sought to use a bridging organization by forming a local homeless task force. An apparent breakdown occurred when the task force was unable to articulate integrative values and a vision for the community as a whole. The study illustrates the importance of establishing a set of shared values and vision and emphasizes the importance of the establishment of bridging organizations with power and authority to negotiate and implement changes. It challenges the utilization of sociospatial and relational mechanisms, which are designed to physically shift the homeless from the area.